Report of chronic myeloid leukemia from All India Institute of Medical Sciences, 1990-2010 - Mishra, Pravas; Seth, Tulika; Sazawal, Sudha; Mahapatra, Manoranjan; Saxena, Renu (Indian Journal of Medical and Paediatric Oncology, 2013)
All India Institute of Medical Sciences, New Delhi is an Apex Institute and caters to more than 1.5 million out-patients and 80,000 in-patients every year. In this study, we have presented data of patients over a period of 20 years. This encompasses our initial experience with hydroxyurea, then interferon alone or with cytarabine and finally imatinib. We have presented data of 525 patients treated on imatinib alone. Imatinib dose was increased in 56 (10.6%) patients and regain of complete hematological response was seen in 26 patients. A total of 14 patients were transplanted for different indications of chronic myeloid leukemia and out of which 12 patients are doing well, while two died due to Grade IV gut graft-versus-host disease.
Keywords: Chronic myeloid leukemia; All India Institute of Medical Sciences; Imatinib